Learning to Disclose: Disclosure Dynamics in the 1890s Streetcar Industry - Bourveau, Thomas; Breuer, Matthias; Stoumbos, Robert (Review of Financial Studies, 2025)
Abstract We study the influence of bounded rationality on companies’ disclosure to investors in new industries. Using a historical example of a new industry, we document that several companies initially withheld their earnings, despite external capital needs and investor information demands. However, almost all these companies started disclosing shortly thereafter. Interpreted through the lens of a disclosure model featuring level-$ k $ thinking, these patterns suggest that limited strategic thinking of some companies contributed to the initial failure to disclose, while feedback and learning over time contributed to the quick convergence to an equilibrium of (almost) full disclosure in the new industry.